Comparative nonlinear seismic analysis of an existing RC bridge designed with obsolete codes. Issue 7 (May 2022) - Nanclares, Germán; Ambrosini, Daniel; Curadelli, Oscar
The evolution of seismic design and calculation criteria for highway bridges has a direct influence on their structural behavior. This paper presents a nonlinear dynamic analysis using a detailed 3D finite element model of an existing bridge, with different design criteria for the column transverse reinforcement, according to code requirements of different times. The numerical model is able to simulate both the collapse of the structure and the generation of damage in its elements when subjected to extreme seismic actions. Through the numerical model, it is possible to represent the cyclic behavior of the concrete, and to evaluate the influence of the transverse reinforcement assigned to the column on the overall response of the bridge. The formation of plastic hinges is verified, as well as the identification of different collapse mechanisms.